Towards Non-Contact Glucose Sensing in Aqueous Turbid Medium at ∼1.1 Meters Distance - Daqing Piao; John O'Hara; Satish Bukkapatnam; Sabit Ekin (IEEE Photonics Journal, 2020)
This work demonstrates a non-contact diffuse reflectance approach with a working distance of ∼1.1 meters for the potential of glucose sensing. Non-contact diffuse reflectance over 1.1–1.3 µm was developed according to a center-illumination-area-detection (CIAD) geometry. The modeled response of diffuse reflectance in the CIAD geometry was examined with phantoms by altering independently the size of the collection geometry and the reduced scattering and absorption properties of the medium. When applied to aqueous turbid medium containing glucose control solutions with the cumulative volume varying over three orders of magnitude, a linear relationship expected for the diffuse reflectance as a function of the medium absorption/reduced-scattering property was observed for four conditions of the glucose-medium composition that differed either in the effective glucose concentration or the host medium scattering property. The cumulation of glucose up to 17.8 mg/dL and 8.9 mg/dL in the host medium having the same optical properties resulted in linear regression slopes of 0.0032 and 0.0030, respectively. The cumulation of the glucose up to 17.8 mg/dL in an aqueous host medium that differed two folds in the reduced scattering property caused the linear regression slope to differ between 0.0032 and 0.0019. The R2 values of all cases were all greater than 0.987.